Microbiomas do solo de viveiros e do intestino do camarão litopenaues vannamei relacionados ao uso de probióticos na carcinicultura - Costa, Samantha Pinheiro da (2015)
Initially, this study analyzed the microbial composition and micro-organism cell count of a commercial probiotic used in a shrimp farm in Ceará, whose composition is unknown, by dependent and independent methods. The results showed the presence of the bacteria genera of Lactobacillus, Acetobacter and Streptococcus and Saccharomyces yeast. The monitoring of the probiotic management showed that after 15 days the product contained almost exclusively representatives of Lactobacillus and Saccharomyces, being the population of yeasts more numerous than bacteria. As conclusion, this study showed that the handling changes the composition of the initial product and that the microbial composition does not justify the application suggested by the manufacturer for treating soil and water. In order to verify the consequences of long term use of probiotics in shrimp farming and its possible effects on the microbial taxonomic and functional composition in Litopenaeus vannamei shrimp gut and pond soils, two farms were selected: one that use probiotics which are mainly constituted by bacteria from the genus Bacillus (phylum Firmicutes), since 2004 and another two ponds used as reference, where do not use probiotics products. Chemical composition and particle size of the soil analyses were accomplished and positive correlations were verified between the farm that use probiotics and the following abiotic variables: silt-clay, organic carbon, organic matter, manganese and carbon/nitrogen ratio. The taxonomic and functional diversity of microbial communities in gut shrimp and soil were accessed by sequencing of metagenomic and gene fragments of 16S rRNA libraries using the platform "Miseq" of Illumina. The metagenomic data showed that the intestine and shrimp ponds soil shared five phyla of bacteria (Proteobacteria, Cyanobacteria, Bacteroidetes, Firmicutes, Actinobacteria) and one phylum of Archaea (Euryarchaeota), and that phylum Firmicutes predominates in the samples obtained from soil and animals whose uses probiotics. Nevertheless, no significant changes were detected in the metabolic profile of those microbiomes (soil and intestine). Sequencing of the fragments of 16S rRNA gene showed that all samples of soil shared seven phyla (Proteobacteria, Bacteroidetes, Chloroflexi, Firmicutes, Planctomycetes, spirochaetes and Acidobacteria), and over again the Firmicutes phylum had higher abundance when compared which those that do not use probiotics in ponds. The Archaea domain showed, for the first time in this study, two others phyla (Crenarchaeota and Parvarchaeota) besides the Euryarchaeota phylum. Despite the differences observed in the taxonomic composition, the diversity indices highlight for the maintaining of diversity in soils, regardless of the treatment used. The Proteobacteria phylum (consisting of Gram-negative bacteria) was the only habitat specialist shared by all pond soils, and the Firmicutes phylum (composed of Gram-positive bacteria) has emerged as one of habitat specialists for the pond where the probiotics are applied. Our results demonstrate the contribution of benthic habit of L. vannamei for the gut microbiome of adult shrimps, and also indicate that long term use of probiotics can change the structure of the microbial community, suggesting the need for diagnostic actions and monitoring of the use of probiotics in Brazil.